2021
DOI: 10.1111/jocn.16131
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐practice context exploration of nursing preparedness and comfort to care for people with intellectual disability and autism

Abstract: Aims and Objectives To compare the self‐perceived preparedness, knowledge, comfort and confidence of Australian Registered Nurses when caring for people with ID and/or ASD across contexts of practice: primary care and community, intensive care, acute hospital, emergency department, paediatrics and ID/ASD. Background There is limited research comparing nursing preparedness and competency when caring for people with intellectual disability (ID) and/or autism (ASD) across nursing contexts of practice. A greater u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…A study into the efficacy of an online Continuous Practice Development program focused on nursing care of people with Intellectual Disability and/or autism in mainstream health settings, which involved synchronous and asynchronous learning opportunities, demonstrated statistically significant difference in self-reported comfort, confidence, and preparedness to provide care to people with Intellectual Disability and/or autism as compared with baseline (Cashin et al, 2023). Further study is needed, but it is likely that increasing appropriate undergraduate and post graduate content in nursing program will achieve similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study into the efficacy of an online Continuous Practice Development program focused on nursing care of people with Intellectual Disability and/or autism in mainstream health settings, which involved synchronous and asynchronous learning opportunities, demonstrated statistically significant difference in self-reported comfort, confidence, and preparedness to provide care to people with Intellectual Disability and/or autism as compared with baseline (Cashin et al, 2023). Further study is needed, but it is likely that increasing appropriate undergraduate and post graduate content in nursing program will achieve similar outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…This reality extends to nurses having low levels of awareness and knowledge related to Intellectual Disability and/or autism (Appelgren et al, 2018), as well as feeling unprepared to care for people with Intellectual Disability and/or autism (Howie et al, 2021). For instance, a national survey of 693 Australian Registered Nurses, the largest survey of nurses related to care of people with Intellectual Disability and/or autism identified internationally, reported that nurses have low levels of relevant educational experience and self‐perceived confidence and competence when caring for people with Intellectual Disability and/or autism in mainstream health settings (Cashin, Pracilio, Buckley, Kersten, et al, 2022; Cashin, Pracilio, Buckley, Morphet, et al, 2022). Additionally, a self‐perceived knowledge deficit in nurses in the concept of making reasonable adjustments to practice was identified (Wilson et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The intellectual disability health sector in Australia has strong roots in primary care, where a lot of early research and pivotal work around the utility of health assessments was undertaken (e.g., Lennox et al, 2010). More recent research has focused on understanding knowledge and skill gaps in our health workforce (e.g., Cashin et al, 2022) and describing how people with intellectual disability use our health system to inform service planning (e.g., Srasuebkul et al, 2021). Groundwork, including Medicare reimbursement and collation of evidence of effectiveness, has been laid to support routine application of comprehensive annual health assessments by GPs.…”
Section: An Emerging Evidence Base For Healthcare For People With Int...mentioning
confidence: 99%
“…A supported interprofessional discussion with disabled people enabled a critical reflection on the merits and limitations of the social and biomedical models of disability and health [55]. For already practicing HPs, these personal and professional strategies might also prove valuable, especially for HPs who have not specialized in working with a specific disabled population (for example, intellectual disability) and who demonstrate more negative attitudes and emotions towards these people, compared to HPs who benefit from greater exposure whilst working [22,23,27,28].…”
Section: Experiential Learning Opportunities For Student Hpsmentioning
confidence: 99%
“…Similar to practicing HPs, these behaviors arose from a lack of confidence with approaching disabled people and a feeling of being 'overwhelmed' due to a lack of training with positive disability-specific experiential learning opportunities [15]. Previous surveys of registered nurses have shown preparedness via upskilling and postgraduate learning opportunities is associated with more comfort and knowledge to care for people with intellectual disability and autism [27,28].…”
Section: Introductionmentioning
confidence: 99%